Technology-Enhanced Knowledge Management Framework for Retaining Research Knowledge among University Academics - Rambe, Patient; Mbeo, Mpho Agnes (Journal of Economics and Behavioral Studies, 2017)
Given the challenge of retaining the research knowledge of an aging, experienced professoriate at South African Universities of Technology, institutions with a nascent tradition of scholarly research, this paper explores the feasibility of a technology-enhanced knowledge management framework for generating, sharing and retaining tacit research knowledge to leverage research outputs at the Central University of Technology (CUT), Free State, South Africa. Since digital trails of established-novice researcher interactions are left behind whenever they interact in online platforms, an examination of such interactions can provide insights into the sharing and transferring of tacit research knowledge from senior researchers to novices. This theoretical study draws on Nonaka and Takeuchi’s Theory of Organisational Knowledge Creation, an emerging technology platform, SharePoint, mainstream literature and the authors’ reflective experiences to develop a technology-enhanced knowledge management model. The paper argues that tacit knowledge can be assimilated from a comprehensive examination of the knowledge production interactions between senior academics and novices enabled by low threshold technology and collaborative sharing of content. This study’s insights are relevant to Higher Educational Institutions (HEIs) struggling to create a sustainable culture of scholarly research and grow a new generation of competent researchers amid the attrition of senior academics and the prevalence of systemic blockages in knowledge transfer processes.